Batik Smock at The Galbita Gallery Home Industry in Banaran Village, Sukoharjo, Central Java - Safitri, Nandini Ayu; Zuhro, Aida Roihana (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
This study aims to describe the process of making batik smocks produced by the Galbita Gallery Home Industry. This research is a descriptive qualitative research. This research is focused on the comparison of smock techniques in fabrics with batik combined with smock techniques. Data collection was obtained by observation, interview, and documentation techniques. The subject of this study is Home Industry Galbita Gallery, and the object of the research is the batik smock at Home Industry Galbita Gallery. The research instruments are the researcher himself accompanied by observation guidelines, interview guidelines, and documentation guidelines, as well as using voice recording aids, cameras, and notebooks. The technique of checking the validity of the data was obtained by triangulation. Data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study show that batik smocks are made at Home Industry Galbita Gallery by combining two techniques, namely the smock technique and the batik stamp technique. The smock and batik combination smock technique produces fabrics with different uniqueness and aesthetic value. The smock technique offers an elegant three-dimensional texture, while the combination of smock and batik creates a fabric with richer and more artistic dimensions and colours. Both are valued in the world of textiles and fashion because of their uniqueness and high added value.